2010
DOI: 10.1021/ml100008s
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Site Thermodynamics Explain SARs for Triazolylpurines Analogues Binding to the A2A Receptor

Abstract: A series of triazolylpurine analogues show interesting and unintuitive structure-activity relationships against the A2A adenosine receptor. As the 2-substituted aliphatic group is initially increased to methyl and isopropyl, there is a decrease in potency; however, extending the substituent to n-butyl and n-pentyl results in a significant gain in potency. This trend cannot be readily explained by ligand-receptor interactions, steric effects, or differences in ligand desolvation. Here, we show that a novel meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 27 publications
5
90
0
Order By: Relevance
“…Lenzi et al [35] showed the presence of hydrophobic residues in the binding access site of the hA 3 AR, whereas in the binding pocket gate of the hA 2A AR, there are some ionic residues. [36] On the other hand, the hypothetical binding mode for compounds 11-13 in the hA 1 AR is more similar to the pose previously reported for compounds 1-10. The oxopropoxy group is located in the upper region, whereas the aryl ring is located in the bottom of the pocket in a similar region as the furan ring of the co-crystallized ligand ZM241385 in the 3EML hA 2A AR crystal structure (Figure 4 a).…”
Section: Molecular Docking Studiessupporting
confidence: 79%
“…Lenzi et al [35] showed the presence of hydrophobic residues in the binding access site of the hA 3 AR, whereas in the binding pocket gate of the hA 2A AR, there are some ionic residues. [36] On the other hand, the hypothetical binding mode for compounds 11-13 in the hA 1 AR is more similar to the pose previously reported for compounds 1-10. The oxopropoxy group is located in the upper region, whereas the aryl ring is located in the bottom of the pocket in a similar region as the furan ring of the co-crystallized ligand ZM241385 in the 3EML hA 2A AR crystal structure (Figure 4 a).…”
Section: Molecular Docking Studiessupporting
confidence: 79%
“…26 WaterMap calculations were performed on the crystal structure of D3R (Figure S2) and on representative frames from the D3R- and D2R- 2 MD trajectories (Figure 2c and d). …”
Section: Experimental Methodsmentioning
confidence: 99%
“…To generate a WaterMap for each receptor, the ligand is removed, a molecular dynamics simulation is carried out, and regions of water density that substantially exceed bulk density are identified as quasilocalized water sites [22][23][24][25][26][27][28]. The free energy required to displace these waters is estimated from a modified version of inhomogeneous solvation theory (IHT) [29][30][31]; various computational benchmark calculations and comparison with experimental data have established that the IHT approximation is a reasonably good one.…”
Section: Methodsmentioning
confidence: 99%